Thermal Emission from Binary Millisecond Pulsar Stars (MSPs) - Albakri, Sundus (Iraqi Journal of Science, 2023)
Pulsar stars divided into two types depending on the periods of rotation, normalemission Pulsar and Millisecond pulsars (MSPs). In this paper, the effect of thestrong magnetic field on the thermal emission in Millisecond pulsar stars isconcentrated. Also the luminosity spin down (Lsp) are calculated depends on theperiods (P), and Period derivative (P) for sample stars which were adopted. Therelation between internal and surface magnetic field is illustrated. The model thatwhich adopted is Hallo Cone Model (HCM)). The total magnetic dipole radiationpower (heating power Wh) of all super fluid neutrons in MSPs stars is calculated.For sample stars of MSPs , the value of transition period (Ptr) was determined bydepending on the some properties of pulsar star. The results indicated that heatingpower of our model (A) would be larger than the model (B) that’s due to the hugevalue of the moment of inertia (I). Also the results showed that the maximumsurface luminosity of stars occurs at the values of Magnetic field ≥ 5.5 1012 Gauss.